2000
DOI: 10.7863/jum.2000.19.5.303
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Doppler RI: impact of renal arterial distensibility on the RI in a hydronephrotic ex vivo rabbit kidney model.

Abstract: The aim of this study was to evaluate the influence of elevated ureteral pressure on renal arterial distention, and thereby on the Doppler resistive index. Seven isolated rabbit kidneys were subjected to a pulsatile perfusion while the renal pelvis was pressurized via the ureter. Renal vascular pressure, flow, resistance (pressure/flow) and conductance (flow/pressure) were compared to simultaneous resistive index measurements using linear regression analysis. Changes in the Conductance Index (systolic conducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 24 publications
4
60
0
Order By: Relevance
“…Renal circulation cannot be directly assessed in humans, but renal flow in interlobular arteries can be evaluated using RI and Doppler sonography (13,16). This method provides an indirect indication of blood flow and therefore may be somewhat variable, although we obtained good reproducibility for day-to-day measurements (see Methods).…”
Section: Fig 3 Relationships Between Changes In Number Of Chymase-pmentioning
confidence: 88%
“…Renal circulation cannot be directly assessed in humans, but renal flow in interlobular arteries can be evaluated using RI and Doppler sonography (13,16). This method provides an indirect indication of blood flow and therefore may be somewhat variable, although we obtained good reproducibility for day-to-day measurements (see Methods).…”
Section: Fig 3 Relationships Between Changes In Number Of Chymase-pmentioning
confidence: 88%
“…The first is the significance of the resistive index values and variations, which remains unclear because the relationship between this parameter and renal vascular resistances seems to be poor, perhaps due to a large number of additional factors implicated in AKI [38,39,[53][54][55][56]. Indeed, experiments performed on models of ex vivo kidneys have confirmed a major role for vascular compliance (modification in vascular diameter following changes in pressure) or pulse pressure as a determinant of the resistive index [54][55][56]. These experimental data have been recently confirmed in kidney-transplanted patients [57].…”
Section: (Experts Opinion) Strong Agreementmentioning
confidence: 99%
“…In fact, elevations in hsCRP have been associated with reduced arterial elasticity 27 and increased arterial stiffness measured by pulse wave velocity (PWV), 28,29 and the relationship between hsCRP and IMT as an early marker of atherosclerosis was shown. 30,31 Moreover, a strict dependence of RRI from arterial stiffness was demonstrated in experimental studies, 8,26 and an association was confirmed between RRI and PP, 21,[32][33][34][35] and between RRI and PWV. 33,36 A relationship between RRI and IMT was also reported.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, tubules and interstitium, rather than glomerular capillaries, are considered to constitute the initial site of kidney injury, 25 and a common feature of experimental models of salt-sensitive hypertension is the existence of tubulo-interstitial inflammatory infiltration, in addition to intrarenal arteriolopathy. 13 In particular, the experiment by Murphy et al 26 showed 21 (33) 8 (38) 13 (31) 16 (37) Ca-channel blockers (n (%)) 6 (9) 3 (14) 4 (10) 5 (12) Diuretics (n (%))…”
Section: Discussionmentioning
confidence: 99%